Association of enhanced circulating trimethylamine N‐oxide with vascular endothelial dysfunction in periodontitis patients. Issue 5 (3rd November 2021) - Zhou, Jiamin; Chen, Shan; Ren, Jing; Zou, Huiqiong; Liu, Yafang; Chen, Yanbin; Qiu, Yumin; Zhuang, Weijie; Tao, Jun; Yang, Junying
Abstract: Background: Accumulating evidences indicate that periodontitis is closely associated with endothelial dysfunction. Trimethylamine‐N‐oxide (TMAO), a harmful microbiota generated metabolite, has been implicated as a nontraditional risk factor for impaired endothelial function. However, whether increased circulating levels of TMAO in periodontitis patients induces endothelial dysfunction remains unknown. Methods: Patients with periodontitis and periodontally healthy controls were enrolled. Periodontal inflamed surface area (PISA) was calculated to assess the inflammatory burden posed by periodontitis. The circulating TMAO was measured by high‐performance liquid chromatography with tandem mass spectrometry (HPLC‐MS/MS). Vascular endothelial function including peripheral endothelial progenitor cells (EPCs), brachial arterial flow‐mediated vasodilation (FMD), and brachial‐ankle pulse wave velocity (baPWV) were assessed. We also isolated and cultured EPCs from participants' peripheral blood to investigate the effect of TMAO on EPC functions in vitro. Results: One hundred and twenty two patients with Stage III‐IV periodontitis and 81 healthy controls were included. Patients with periodontitis presented elevated TMAO ( P = 0.002), lower EPCs ( P = 0.025), and declined FMD levels ( P = 0.005). The TMAO concentrations were correlated with reduced circulating EPCs and FMD levels. Moreover, TMAO can injury EPCs function in vitro, and may induce cell pyroptosis via Bax/caspase‐3/GSDME pathway. Conclusions: The present study demonstrates for the first time that circulating TMAO levels are increased in patients with Stage III‐IV periodontitis, and correlated with vascular endothelial dysfunction. These findings may provide a novel insight into the mechanism of vascular endothelial dysfunction in patient with periodontitis via TMAO‐downregulated EPC functions.